CDKAL1 SNPs (rs10946398 and rs9356744) Variations in type 2 diabetes and its association with some glycemic parameters - Teiba Mohammed Kazeam AL-Abudy; Mona N. AL-Terehi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: CDKAL1 is one of the most often discovered genes linked to risk Across a wide range of ethnic groups, investigations of genome-wide associations indicate that the gene CDKAL1 has a number of SNPs that raise the risk of type 2 diabetes (T2D). Objective: Study the association between type 2 diabetic (T2DM) and CDKAL1,Study the effect life style on the patient of type 2 diabetic (T2DM) and Describe the association betweenCDKAL1 and T2DM pathophysiology Methodology : a case control study these study contours 50sample control and 60 patients, Physiological parameters were measured and flanking sequencing Result: the results showed according to diet control all parameters (age, Body Mass Index (BMI), duration, Fasting Blood Glucose (FBG), HemoglobinA1c(HBA1C), , Insulin hormone(IN), insulin resistance(IR), and insulin sensitivity (IS) are nonsignificant in control and patients (p<0.05) . in study subjects according to family history all parameters. Age , BMI, duration, FBG , HBA1C , IN and IR, are not significant while IS is significant. in study subjects according to physical activity all parameters age, BMI, duration, FBG, HBA1C, IN, IR, and IS are nonsignificant in control and patients, . the CDKAL1 genotyping showed cdkrs10946398 and cdkrs9356744 is nonsignificant. Conclusion: no significant association between (cdkrs10946398 and cdkrs9356744)in CDKAL1 Gene and Physiological parameters age, duration , BMI , FBG , HBA1C , IN , IR and IS.